Equity in Public Services in Tanzania and Uganda - World Bank (Washington, DC, 2013)
The context of this note is the concern in both Uganda and Tanzania that the distribution of public servants in both countries has been uneven, leading to inequity in the delivery of public services, with lower quality services linked to persistent poverty in certain underserved or hard-to-reach and stay (HTRS) areas. The note looks in detail at the nature of the problem as it affects education and health services, assesses measures already in place to tackle inequity, and makes recommendations to address the problem in the immediate as well as the long-term. In focus in this note are those areas that suffer from having far below average numbers of public servants, and consequently far below average public services. In Tanzania such areas are more commonly referred to as under-served and again additional resources have been allocated to them. Governments have so far responded with relatively conventional measures, such as financial incentives for staff and improved living conditions. While both of these are important, the scope and depth of the issue requires a more radical approach. A range of ideas is offered for each country, and these are then presented in a matrix. Three priorities needs emerge for both countries: 1) to consider demand as well as supply-side measures, in particular to strengthen Government accountability; 2) to address fiscal constraints by changing policies on allowances which currently favor those at the centre of government, and by giving HTRS areas greater financial management flexibility; and 3) to put a time limit on the assessment of measures to fix the state, leaving open the possibility that market mechanisms might eventually present the best option in dealing with inequity in public services.